HUBUNGAN PERSEPSI EFEK SAMPING IUD, DUKUNGAN SUAMI DAN KEPRAKTISAN IUD DENGAN KEIKUTSERTAAN AKSEPTOR IUD DI KELURAHAN JATISARI KECAMATAN MIJEN KOTA SEMARANG TAHUN 2016 - Imani Lia Purnandias; Atik Mawarni; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2018)
Indonesia is one of the developing countries with various types of problems. The main problem in Indonesia is the demography area which is the high population growth rate. The average growth per year of Indonesia's population during the period 2010-2015 at a population growth rate of 1.38%. According to the 2012 IDHS data indicating TFR has not reached the target (2.36). There is a difference from the target with the SDKI (2.6). This dispute proves that the family planning program has not been successful. The reason why the family planning program has not been successful in the community is to reject the family planning, which is fearing the side effects of contraceptive use. The purpose of the study is to analyze the relationship of perception of adverse effects of IUD, husband support and IUD practicability with IUD acceptor participation. Type and Design The research is explanatory research with cross sectional study approach. The case population was women of fertile couples aged 20 to 49 using contraceptive contraception with 1380 acceptors. This technique uses cluster method with proportional random sampling. The sample of research is 83 respondents. Statistical test using univariate test and bivariate test, so that the appearance of nominal data scale. Scale data on the research is nominal - nominal, then the statistical test using Chi Square. The result of univariate and bivariate test showed that young age (53,0%), age of first marriage (59,0%), advanced education (92,8%), unemployment (80,7%), perception of adverse side effect of IUD (59.0%), husbands did not support (72.3%), IUD practicability (72.3%). The result of statistical test of Chi Square test (α = 0,05) showed that the relation of perception of IUD side effect with IUD acceptor participant with pvalue = 0,563 value with 95% CI = 0,594 - 3,449. while the support of the husband with the participation of IUD acceptors with pvalue value = 0.001, with 95% CI = 0,594 - 3,449, and IUD practicability with IUD acceptors acceptance with pvalue = 0,004 value with 95% CI = 1,767 - 16,506. The conclusion of this research is that there is no correlation between perception of IUD side effect with IUD acceptor participant, pvalue value (> α = 0,05) and husband support relationship and IUD practicability with IUD acceptor participation, niali pvalue (<α = 0,05) .Suggestion Provide interpersonal communication to women fertile couple and explanation of IUD.